MEMAHAMI PERAN DAN FUNGSI PERKEMBANGAN PESERTA DIDIK SEBAGAI UPAYA IMPLEMENTASI NILAI PENDIDIKAN KARAKTER DALAM KURIKULUM - Heri Cahyono; Iswati Iswati (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
The students need to plant good characters because the planting of characters must start early, because it will be easier to form. The existing character values of 18 points must absolutely be implemented in each subject and by the level of educational unit. Implementation is by integrating into learning activities with approaches that make learners as their subject. To see the success of this character education implementation, it is necessary to have a good assessment in every subject, class or school in general and the teacher is the leader in value-based learning activities of the nation character, to support the optimization of teacher’s role in the integration of character values in learning activities, teachers should have an insight into the knowledge and experience of the values contained in the nation’s character broadly and adequately.